Global research trends in neurosyphilis: a bibliometric analysis from 2010 to 2024 - Wei, Wei; Li, Wei (Frontiers in Immunology, 2025)
BackgroundNeurosyphilis, as a serious infectious disease caused by Treponema pallidum invading the central nervous system, has seen a significant increase in global incidence in recent years. However, the trends and gaps in the research of neurosyphilis remain unknown.ObjectiveBibliometrics was adopted to analyze the research trends of neurosyphilis from 2010 to 2024, and to identify the core themes, hotspots and development directions.MethodsResearch related to neurosyphilis from 2010 to 2024 was retrieved in the Web of Science core Collection (WOSCC). Bibliometrix, VOSviewer, CiteSpace, and BioBERT language models were employed to perform bibliometric and knowledge mapping analyses on global research output, author/institution collaboration networks, keyword evolution, co-citation clusters, and associated genes in the field of neurosyphilis.ResultsA total of 863 articles were included in the analysis. From 2010 to 2024, both the number of publications and citations demonstrated a rapid upward trend. The United States and China were the leading contributors in the field of neurosyphilis research, accounting for 27.3% and 26.9% of global publications, respectively. The University of Washington and Xiamen University emerged as the most prolific research institutions. Keyword analysis identified “ cerebrospinal fluid (CSF),” “ human immunodeficiency virus (HIV),” “ocular syphilis,” and “general paresis” as core research topics. Research focus has gradually shifted from traditional diagnostic criteria and penicillin-based treatment approaches to investigations into immune mechanisms, co-infection factors, and the identification of novel biomarkers. In recent years, the appearance of keywords such as “case report,” “gene expression,” and “transcriptomics” indicates a growing emphasis on precision medicine and molecular mechanisms. The increasing frequency of immune-related molecules, including CD4, CXCL13, and IL-6, suggests that the mechanisms underlying immune responses may represent a promising direction for future research breakthroughs.ConclusionsResearch on neurosyphilis is transitioning from traditional clinical descriptions toward multidisciplinary precision medicine. Future efforts should focus on integrating multi-omics technologies, establishing globally unified diagnostic criteria, and enhancing international collaboration to address the public health challenges posed by this disease.